ANALYSIS OF THE TYPES OF PROVIDING EDUCATIONAL SERVICES TO SUPPORT INNOVATIVE ENTREPRENEURSHIP IN PERSONNEL TRAINING MANAGEMENT (Marketing Journal, 2025)
The article analyzes the functioning mechanisms of human resource training management, particularly the types of ensuring its economic interrelation with innovative entrepreneurial activity. Specifically, based on a comparative analysis of different types of human resource training management, opportunities for the development of innovative entrepreneurial activity have been identified.
Keywords: management; human resource training; human resource training management; professional competence; higher education services; labor market; education system; innovation; innovative activity; entrepreneurship; innovative entrepreneurship